Agriculture for Economic Development in Africa Evidence from Ethiopia - Rohne Till, Emelie (Springer Nature, 2022)
This book explores the role of agriculture in long-term economic growth. With a particular focus on Ethiopia, the role of the state in igniting agricultural growth and in sustaining economic growth is highlighted as essential for low-income countries. Taking ideas from both economic history and development economics, the ability of Ethiopia and the rest of Africa to sustain recent rapid growth into something that can tackle the development agenda is discussed, alongside policy suggestions. This book overall presents an optimistic account of Africa and its economic prospects. It will be relevant to students and researchers interested in economic development and agricultural economics. This is an open access book.